Nanoparticle-Based Drug Delivery for Vascular Applications - Naskar, Atanu; Kilari, Sreenivasulu; Baranwal, Gaurav; Kane, Jamie; Misra, Sanjay (Bioengineering (Basel), 2024)
Nanoparticle (NP)-based drug delivery systems have received widespread attention due to the excellent physicochemical properties of nanomaterials. Different types of NPs such as lipid NPs, poly(lactic-co-glycolic) acid (PLGA) NPs, inorganic NPs (e.g., iron oxide and Au), carbon NPs (graphene and carbon nanodots), 2D nanomaterials, and biomimetic NPs have found favor as drug delivery vehicles. In this review, we discuss the different types of customized NPs for intravascular drug delivery, nanoparticle behaviors (margination, adhesion, and endothelium uptake) in blood vessels, and nanomaterial compatibility for successful drug delivery. Additionally, cell surface protein targets play an important role in targeted drug delivery, and various vascular drug delivery studies using nanoparticles conjugated to these proteins are reviewed. Finally, limitations, challenges, and potential solutions for translational research regarding NP-based vascular drug delivery are discussed.